Male bluegill vary in color and behavior relative to their position in a lek - Peroš, Matthew; Vij, Lakshita; Anavian, Elana; Almeida Arteaga, Kevin; Haruna, Fatima Iya; Siegman, Aliza; Fang, Wei; Alvarado, Sebastian Gaston (Frontiers in Ethology, 2025)
Animals organize into social groups to increase collective fitness. These groups use behavior and morphological traits like color to communicate social status. Male bluegill (Lepomis macrochirus) form breeding collectives during the reproductive months. However, whether these colonies generate resource-stratified social hierarchies to manage intrasexual competition is unknown. We hypothesize that territorial position within the colony results in different body colors and behavioral profiles. To test this hypothesis, we quantified color patterns in wild communities of bluegill using computer vision, scored the behavior of lek occupying parental males, and categorically classified lek position as a function of neighboring males. From these data, we show that body coloration and behavior vary with lek position, suggesting a division of labor in the construction and maintenance of grouped territories where courtship and sexual selection take place. Collectively, these data underline the importance of male-specific morphological plasticity and its impacts on social organization.